2020
DOI: 10.21203/rs.2.19894/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictive models for Talaromyces marneffei infection in HIV-infected patients using routinely collected data

Abstract: ObjectivesLate diagnosis of Talaromyces marneffei (T. marneffei) in patients with HIV/AIDS infection is strongly associated with greater mortality. To date, effective predictive model for T. marneffei infection in clinical practice have not been established. We aimed to identify a non-culture-based method for rapid detection of T. marneffei infection in HIV/AIDS patients.MethodsThe prediction models were initially constructed using patients in a retrospective cohort study. We obtained demographics, clinical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Nevertheless, researchers have noted that in Southeast Asia, HIV-negative patients who possess the HLA-DR*15:02/16:02 and HLA-DQ*05:01/05:02 genes are predisposed to T. marneffei infection [ 29 ]. In HIV-infected individuals, a prediction model has been developed to produce accurate clinical outcome assessments based on the associations between T. marneffei infection and the clinical features of HIV infection [ 70 ]. Thus, candidate factors such as skin lesions, AST level, ALT ratio index, peripheral or abdominal lymphadenopathy, and CD4+ T-cell counts were all considered in different prediction models.…”
Section: Diagnosis Of Talaromycosismentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, researchers have noted that in Southeast Asia, HIV-negative patients who possess the HLA-DR*15:02/16:02 and HLA-DQ*05:01/05:02 genes are predisposed to T. marneffei infection [ 29 ]. In HIV-infected individuals, a prediction model has been developed to produce accurate clinical outcome assessments based on the associations between T. marneffei infection and the clinical features of HIV infection [ 70 ]. Thus, candidate factors such as skin lesions, AST level, ALT ratio index, peripheral or abdominal lymphadenopathy, and CD4+ T-cell counts were all considered in different prediction models.…”
Section: Diagnosis Of Talaromycosismentioning
confidence: 99%
“…Thus, candidate factors such as skin lesions, AST level, ALT ratio index, peripheral or abdominal lymphadenopathy, and CD4+ T-cell counts were all considered in different prediction models. It was observed that the model combining AST levels and the ALT ratio index displayed high power, specifically for the early diagnosis of T. marneffei infection [ 70 ]. Although this work has only been published in a preprint research platform, the approach used to conduct the investigation is impressive, and may well be improved upon using a higher volume of, and more frequently collected data obtained from clinical practice.…”
Section: Diagnosis Of Talaromycosismentioning
confidence: 99%